Designing Ultraflexible Perovskite X‐Ray Detectors through Interface Engineering. Issue 24 (13th November 2020) - Demchyshyn, Stepan; Verdi, Matteo; Basiricò, Laura; Ciavatti, Andrea; Hailegnaw, Bekele; Cavalcoli, Daniela; Scharber, Markus Clark; Sariciftci, Niyazi Serdar; Kaltenbrunner, Martin; Fraboni, Beatrice
Abstract: X‐ray detectors play a pivotal role in development and advancement of humankind, from far‐reaching impact in medicine to furthering the ability to observe distant objects in outer space. While other electronics show the ability to adapt to flexible and lightweight formats, state‐of‐the‐art X‐ray detectors rely on materials requiring bulky and fragile configurations, severely limiting their applications. Lead halide perovskites is one of the most rapidly advancing novel materials with success in the field of semiconductor devices. Here, an ultraflexible, lightweight, and highly conformable passively operated thin film perovskite X‐ray detector with a sensitivity as high as 9.3 ± 0.5 µC Gy −1 cm −2 at 0 V and a remarkably low limit of detection of 0.58 ± 0.05 μGy s −1 is presented. Various electron and hole transporting layers accessing their individual impact on the detector performance are evaluated. Moreover, it is shown that this ultrathin form‐factor allows for fabrication of devices detecting X‐rays equivalently from front and back side. Abstract : Ultraflexible, lightweight, and highly conformable thin film perovskite X‐ray detectors are presented here. An evaluation of the individual impact on the detector performance of various electron and hole transporting layers is provided. Such devices are passively operated and show a high sensitivity and a remarkably low limit of detection, allowing also for isotropic detection.